Analisis Bibliometrik Dari Istilah ‘Salutogenesis dalam Kebidanan’ - Ari Andriyani; Istri Bartini; Linawaty Linawaty (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2021)
AbstractBackground: The medical view of the entire maternal period calls into question the use of pathogenesis to frame maternity care services. Therefore, adopting a salutogenic model of maternal care can reduce care inequalities and improve the quality of maternity care provided. The concept of salutogenesis was first introduced in the late 1970s by Antonovsky, who focused on the origins of good health rather than the origins of disease. Salutogenesis is an alternative school of thought that encourages healthcare professionals to adopt a more positive and health focused approach in providing perinatal care to women. In the salutogenic approach, a woman's past experiences, both pleasant and unpleasant, are strongly believed to contribute to her perception of life, well-being, and ability to cope with stressful situations such as the perinatal period.Objective: This study explores the topic of salutogenesis in obstetrics through the Google Scholar databaseResearch Methods: This study uses bibliographic information from the Google Scholar article database between 2000 and 2020 using a total sampling technique. Data was extracted using Publih Or Parish, VOS Viewer and Mendeley Desktop Keywords: salutogenesis, obstetrics, bibliometric, Publish Or Parish, VOSViewer